2022
DOI: 10.1155/2022/9479456
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Attenuates Fructose-Induced Nonalcoholic Fatty Liver in Rats via Antioxidant and Anti-Inflammatory Effects: The Role of Angiotensin-Converting Enzyme 2/Angiotensin (1-7)/Mas Receptor Axis

Abstract: Aim. Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome, and if untreated, it may propagate into end-stage liver disease. The classical arm of the renin-angiotensin system (RAS) has a fundamental role in triggering oxidative stress and inflammation, which play potential roles in the pathogenesis of NAFLD. However, the nonclassical alternative axis of RAS, angiotensin- (Ang-) converting enzyme 2 (ACE2)/Ang (1-7)/Mas receptor, opposes the actions of the classical arm, mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…These results indicated that Sp6 may play a role in the pathogenesis of HLD dyskinesia and corneal K-F ring symptoms. The MAS receptor, encoded by the mas1 gene, is observed in microglia and primarily associated with the renin-angiotensin system and the stimulation of anti-inflammatory signaling pathways [ 59 , 60 ]. Microglia have been extensively studied in the context of brain injury as central nervous system guardians [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that Sp6 may play a role in the pathogenesis of HLD dyskinesia and corneal K-F ring symptoms. The MAS receptor, encoded by the mas1 gene, is observed in microglia and primarily associated with the renin-angiotensin system and the stimulation of anti-inflammatory signaling pathways [ 59 , 60 ]. Microglia have been extensively studied in the context of brain injury as central nervous system guardians [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAAS activation is implicated in the pathophysiology of both MAFLD and CVD [ 76 ]. RAAS activation in metabolically active tissues can exert pro-inflammatory effects, mainly via angiotensin II, and is associated with multiple dysfunctional cellular processes, leading to hepatic necro-inflammation and fibrosis [ 76 78 ]. In a retrospective, territory-wide cohort study of 12,327 patients with NAFLD, the authors found that treatment with RAAS inhibitors was associated with a lower risk of liver-related events, liver cancer and cirrhotic complications, though the indication for use of RAAS inhibitors was for vascular and not liver disease [ 79 ].…”
Section: Consensus Statements and Recommendationsmentioning
confidence: 99%
“…[ 6 ] The beneficial effects of Mas activation have been documented in various diseases. [ 7 , 8 , 9 , 10 ] Our previous research revealed that the activation of Mas effectively attenuates hepatocyte death by enhancing fatty acid oxidation during the early stages of mouse AILI. [ 11 ] However, the role of Mas in the AILI microenvironment remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%